POTENSI BUNGA TELANG (Clitoria ternatea L) SEBAGAI Antifungi Candida albicans, Malasezia furfur, Pitosprorum ovale, dan Aspergilus fumigatus DENGAN METODE BIOTEKNOLOGI FERMENTASI KOMBUCHA : POTENTIAL POTENTIAL FLOWER (Clitoria ternatea L) AS Antifungal for Candida albicans, Malasezia furfur, Pitosprorum ovale, and Aspergilus fumigatus USING KOMBUCHA FERMENTATION BIOTECHNOLOGY METHOD - Firman Rezaldi; Eman eman; Fernanda Desmak Pertiwi; Suyamto Suyamto; Sumarlin US (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Telang flower has the potential to inhibit the growth of Candida albicans, Malasezia furfur, Pitosporum ovale, and Aspergilus fumigatus through the kombucha fermentation biotechnology method. The purpose of this study was to determine the antifungal activity of telang flower kombucha at various concentrations of white sugar. The varying concentrations of granulated sugar used in this study were 20%, 30%, and 40% (w/v), each repeated 3 times. The positive control used was kombucha made from green tea. The negative control used was sterile distilled water. The well diffusion method is one of the methods used to test antifungal activity. The fementation of telang flower kombucha has overall antifungal activity. White sugar concentration of 40% kombucha telang flower was the best concentration in inhibiting the growth of fungi as a whole when compared to the concentration of white sugar kombucha telang flower of 20%, 30% and positive and negative controls.